1993
DOI: 10.1037/0882-7974.8.3.339
|View full text |Cite
|
Sign up to set email alerts
|

References in conversation between young and old normal adults.

Abstract: This study compared the way in which young and elderly adults cooperate to achieve a mutually acceptable reference. Pairs of young and elderly interlocutors performed a repeated referential communication task in which they were asked to converse about arranging complex figures in a particular order. With repetition of the task, both partners, regardless of age, needed fewer words and speaking turns to find mutually acceptable references. However, the older Ss were slower to benefit from the repetition and requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
56
2
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 20 publications
7
56
2
1
Order By: Relevance
“…Such behaviour is in line with other findings such as the fact that lexical diversity tends to be higher among older adults than younger adults ( e.g. Hupet, Chantraine, & Nef, 1993). Although the pseudo-words were novel in the present study, age-related language changes may have influenced performance, and may explain why the older adults were more likely to circumlocute.…”
Section: Discussionsupporting
confidence: 92%
“…Such behaviour is in line with other findings such as the fact that lexical diversity tends to be higher among older adults than younger adults ( e.g. Hupet, Chantraine, & Nef, 1993). Although the pseudo-words were novel in the present study, age-related language changes may have influenced performance, and may explain why the older adults were more likely to circumlocute.…”
Section: Discussionsupporting
confidence: 92%
“…For all indicators of performance used, including number of words used, number of speaking turns used, and the use of optimal descriptors, younger dyads were shown to be the most ef cient communicators. Our results thus replicate those of Hupet et al (1993) who tested younger and older unfamiliar dyads using similar materials. Of course, these results could be the direct consequence of older adults' use of a truly collaborative technique and a focus on reducing errors rather than increasing ef ciency: if one veri es and re-veri es one's choices, the number of words and turns used to accomplish the task will necessarily be increased.…”
Section: Discussionsupporting
confidence: 91%
“…That said, these preserved aspects of memory and learning do not alone account for the performance of the older pairs. Recall that without a partner with whom to collaborate and interact the learning across trials is not observed (Hupet & Chantraine, 1992) and that our results here are in contrast to other versions of the collaborative referencing task in aging that do not preserve many aspects of routine social interaction (e.g., familiar partners, visualization of facial expressions and gesture) (Filer & Scukanec, 1995; Hupet et al, 1993). Thus, the benefits of a social and collaborative environment appear to be above and beyond what would be observed in the presence of intact non-declarative memory alone.…”
Section: Discussionmentioning
confidence: 53%
“…Hupet, Chantraine, and Nef (1993) and Filer and Scukanec (1995) found that older adults were inferior to younger adults on a collaborative referencing task. A closer inspection of the procedures of those studies may help explain why different results were obtained.…”
Section: Discussionmentioning
confidence: 99%